Social cohesion, mental wellbeing and health-related quality of life among a cohort of social housing residents in Cornwall: a cross sectional study - Williams, Andrew James (BMC Public Health, 2020)
BACKGROUND: Research and policy have identified social cohesion as a potentially modifiable determinant of health and wellbeing that could contribute to more sustainable development. However, the function of social cohesion appears to vary between communities. The aim of this study was to analyse the levels of, and associations, between social cohesion, mental wellbeing, and physical and mental health-related quality of life among a cohort of social housing residents from low socioeconomic status communities in Cornwall, UK. Social housing is below market-rate rental accommodation made available to those in certain health or economic circumstances. These circumstances may impact on the form and function of social cohesion. METHODS: During recruitment, participants in the Smartline project completed the Short Warwick-Edinburgh Mental Wellbeing Scale, SF-12v2 and an eight item social cohesion scale. Cross sectional regression analyses of these data adjusted for gender, age, national identity, area socioeconomic status, rurality, education, employment, and household size were undertaken to address the study aim. RESULTS: Complete data were available from 305 (92.7%) participants in the Smartline project. Univariable analyses identified a significant association between social cohesion, mental wellbeing and mental health-related quality of life. Within fully adjusted multivariable models, social cohesion only remained significantly associated with mental wellbeing. Sensitivity analyses additionally adjusting for ethnicity and duration of residence, where there was greater missing data, did not alter the findings. CONCLUSIONS: Among a relatively homogeneous cohort, the reported level of social cohesion was only found to be significantly associated with higher mental wellbeing, not physical or mental health-related quality of life. The efforts made by social housing providers to offer social opportunities to all their residents regardless of individual physical or mental health state may support the development of a certain degree of social cohesion. Sense of control or safety in communities may be more critical to health than social cohesion. Additional observational research is needed before attempts are made to alter social cohesion to improve health.